Effective treatments for social anxiety disorder - Carolina Baeza (CAEN, 2007)
Social Anxiety Disorder (SAD), also known as Social Phobia, is now recognised as a chronicand disabling psychiatric condition. The high prevalence and clinical significance of the disease emphasize the need for early recognition and effective treatment. The main current treatment will be presented paying special attention to meta-analyses and studies, which try to differentiate types of interventions, by their efficacy.